PENTINGNYA INTEGRITAS UNTUK MENGURANGI KECURANGAN AKUNTANSI - Rizkika Apriliana; Dekeng Setyo Budiarto (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2018)
This research aimed to get empirical evidence the influence of internal control, integrity and the compliance of accounting rules on the tendency of accounting fraud at the OPD of Kulon Progo Regency. The population of this study wereall of OPD staffat Kulon Progo regency. The sample used was 83 respondent with purposive sampling method. The data was Collected by using questionnaires. The data were analizedwith multiple linear regression. The results of this research show that the integrity has a negative significant effect on the accounting fraud, while internal controls and the compliance of accounting rules has no significant effect on the accounting fraud. Keywords:  internal control, integrity and the compliance to accounting rules, the tendency of accounting fraud.